Biologic Therapies for Asthma and Allergic Disease: Past, Present, and Future - Fernando Ramírez-Jiménez; Gandhi Fernando Pavón-Romero; Juancarlos Manuel Velásquez-Rodríguez; Mariana Itzel López-Garza; José Fernando Lazarini-Ruiz; Katia Vanessa Gutiérrez-Quiroz; Luis M. Teran (Pharmaceuticals, 2023)
The discovery of the mechanism underlying allergic disease, mouse models of asthma, and bronchoscopy studies provided initial insights into the role of Th2-type cytokines, including interlukin (IL)-4, IL-5 and IL-13, which became the target of monoclonal antibody therapy. Omalizumab, Benralizumab, Mepolizumab, Reslizumab, and Tezepelumab have been approved. These biologicals have been shown to be good alternative therapies to corticosteroids, particularly in severe asthma management, where they can improve the quality of life of many patients. Given the success in asthma, these drugs have been used in other diseases with type 2 inflammation, including chronic rhinosinusitis with nasal polyps (CRSwNP), atopic dermatitis, and chronic urticaria. Like the Th2-type cytokines, chemokines have also been the target of novel monoclonal therapies. However, they have not proved successful to date. In this review, targeted therapy is addressed from its inception to future applications in allergic diseases.